Coagulation factor VIIa binds to herpes simplex virus 1‐encoded glycoprotein C forming a factor X‐enhanced tenase complex oriented on membranes. (9th April 2020) - Lin, Bryan H.; Sutherland, Michael R.; Rosell, Federico I.; Morrissey, James H.; Pryzdial, Edward L. G.
Abstract: Background: The cell membrane‐derived initiators of coagulation, tissue factor (TF) and anionic phospholipid (aPL), are constitutive on the herpes simplex virus type 1 (HSV1) surface, bypassing physiological regulation. TF and aPL accelerate proteolytic activation of factor (F) X to FXa by FVIIa to induce clot formation and cell signaling. Thus, infection in vivo is enhanced by virus surface TF. HSV1‐encoded glycoprotein C (gC) is implicated in this tenase activity by providing viral FX binding sites and increasing FVIIa function in solution. Objective: To examine the biochemical influences of gC on FVIIa‐dependent FX activation. Methods: Immunogold electron microscopy (IEM), kinetic chromogenic assays and microscale thermophoresis were used to dissect tenase biochemistry. Recombinant TF and gC were solubilized (s) by substituting the transmembrane domain with poly‐histidine, which could be orientated on synthetic unilamellar vesicles containing Ni‐chelating lipid (Ni‐aPL). These constructs were compared to purified HSV1 TF±/gC ± variants. Results: IEM confirmed that gC, TF, and aPL are simultaneously expressed on a single HSV1 particle where the contribution of gC to tenase activity required the availability of viral TF. Unlike viral tenase activity, the cofactor effects of sTF and sgC on FVIIa was additive when bound to Ni‐aPL. FVIIa was found to bind to sgC and this was enhanced by FX. Orientation of sgC on a lipid membrane was critical for FVIIa‐dependent FX activation. Conclusions: The assembly of gC with FVIIa/FX parallels that of TF and may involve other constituents on the HSV1 envelope with implications in virus infection and pathology.